2021
DOI: 10.4018/jgim.290831
|View full text |Cite
|
Sign up to set email alerts
|

Changing Digital Age in the Wake of COVID-19

Abstract: Virtual teams play a crucial role in today’s knowledge-based organisation for overcoming challenges in our dynamic world, especially in the current situation of the COVID-19 pandemic. Teams play a key role in today’s knowledge-based organization for overcoming challenges in our dynamic world. Drawing on social information processing theory, this study explores the effect of members’ humility and team environment within a leaderless team mainly based on virtual platforms. Their impacts on shared leadership, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…The COVID-19 is a new strain of coronavirus that has never been found in humans before and its powerful transmission exceeds our imagination Xu et al, 2020). On January 31, 2020, the World Health Organization declared the outbreak as an international public health emergency, showing its seriousness (Cho et al, 2022;Mishra et al, 2022). The outbreak drew strong public attention at the beginning of the outbreak; simultaneously, numerous Internet users published their opinions and insights via social networks after it occurred.…”
Section: Case Study and Discussionmentioning
confidence: 99%
“…The COVID-19 is a new strain of coronavirus that has never been found in humans before and its powerful transmission exceeds our imagination Xu et al, 2020). On January 31, 2020, the World Health Organization declared the outbreak as an international public health emergency, showing its seriousness (Cho et al, 2022;Mishra et al, 2022). The outbreak drew strong public attention at the beginning of the outbreak; simultaneously, numerous Internet users published their opinions and insights via social networks after it occurred.…”
Section: Case Study and Discussionmentioning
confidence: 99%
“…With the COVID-19 outbreak, research found that ML (Alimadadi et al, 2020) and AI (Vaishya et al,2020) can integrate and analyze large-scale data on COVID-19 patients to better understand virus transmission patterns. So some scholars studied COVID-19 from the technical aspects of electronic learning, artificial intelligence and big data (Chang et al,2021;Cho et al,2021;Mehla et al,2021). Singh et al (2021) proposed to use computing infrastructure provided by cloud computing and fog computing to control pandemics such as COVID-19.…”
Section: Introductionmentioning
confidence: 99%